Study Habits for English Language Learning in Seventh-Grade Students - Vindas Carmona, Jazmín (2025)
This research focuses on study habits for learning the English language among seventh-grade students. It was conducted at Liceo José Martí, Liceo de Chacarita, and Colegio Técnico Profesional de Puntarenas. Study habits are crucial for the educational process as they assist students in reviewing, reinforcing knowledge, and improving the assimilation of challenging topics. The methodology combines qualitative and quantitative approaches, including documentary research, interviews with teaching staff, non-participatory observations, and surveys. The results indicated a lack of study habits among the students. In summary, the significance of study habits in enhancing students’ academic performance is highlighted. Emphasizing the need for guidance in this aspect.